Assessing the Economic Impact of FASB No. 8 (Book). - Burns, Thomas J.; Meyer, Philip E. (The Accounting Review, 1980)
Reviews the book "Assessing the Economic Impact of FASB No. 8," by John K. Shank, Jesse F. Dillard and Richard J. Murdock.